Quercetin inhibits neutrophil extracellular traps release and their cytotoxic effects on A549 cells, as well the release and enzymatic activity of elastase and myeloperoxidase - Pereira, G. S. [UNESP]; Percebom, I. [UNESP]; Mendes, S. [UNESP]; Souza, P. S. S. [UNESP]; Diniz, L. F. A. [UNESP]; Costa, M. F. [UNESP]; Lopes, B. R. P. [UNESP]; Toledo, K. A. [UNESP] (Instituto Internacional de Ecologia, 2022)
Neutrophil extracellular traps (NETs) were first reported as a microbicidal strategy for activated neutrophils. Through an immunologic response against several stimuli, neutrophils release their DNA together with proteins from granules, nucleus, and cytoplasm (e.g., elastase and myeloperoxidase). To date, NETs have been implicated in tissue damage during intense inflammatory processes, mainly when their release is dependent on oxygen radical generation. Flavonoids are antioxidant and anti-inflammatory agents; of these, quercetin is commonly found in our daily diet. Therefore, quercetin could exert some protective activity against tissue damage induced by NETs. In our in vitro assays, quercetin reduced NETs, myeloperoxidase (MPO), and elastase release from neutrophils stimulated with phorbol 12-myristate 13-acetate (PMA). The activity of these enzymes also decreased in the presence of quercetin. Quercetin also reduced the cytotoxic effect of NETs on alveolar cells (A549 cell line). Further, in silico assays indicated favorable interactions between quercetin and NET proteins (MPO and elastase). Overall, our results demonstrate that quercetin decreases deleterious cellular effects of NETs by reducing their release from activated neutrophils, and diminishing the enzymatic activity of MPO and elastase, possibly through direct interaction.

As armadilhas extracelulares de neutrófilos (NETs) foram relatadas pela primeira vez como uma estratégia microbicida para neutrófilos ativados. Por meio de uma resposta imunológica contra vários estímulos, os neutrófilos liberam seu DNA ligado a proteínas de grânulos, núcleo e citoplasma (por exemplo, elastase e mieloperoxidase). Até o momento, os NETs têm sido implicadas em danos aos tecidos durante processos inflamatórios intensos, principalmente quando sua liberação depende da geração de radicais de oxigênio. Os flavonóides são agentes antioxidantes e anti-inflamatórios, e destes, a quercetina é comumente encontrada em nossa dieta diária. Portanto, a quercetina pode exercer alguma atividade protetora contra o dano tecidual induzido por NETs. Em nossos ensaios in vitro, a quercetina reduziu a liberação das NETs, mieloperoxidase (MPO) e elastase a partir de neutrófilos estimulados com forbol 12-miristato 13-acetato (PMA). A atividade dessas enzimas também foi diminuída na presença de quercetina. A quercetina também reduziu o efeito citotóxico dos NETs sobre células alveolares (linha celular A549). Além disso, os ensaios in silico indicaram interações favoráveis entre a quercetina e as proteínas da NET (MPO e elastase). No geral, nossos resultados demonstram que a quercetina diminui os efeitos deletérios das NETs, reduzindo sua liberação à partir de neutrófilos ativados e diminuindo a atividade enzimática de MPO e elastase, possivelmente por meio de interação direta.
Quercetina inibe a liberação das armadilhas extracelulares dos neutrófilos e a atividade tóxica delas sobre células A549
Keywords: inflammation; damaged tissue; flavonoids; quercetin; myeloperoxidase; elastase; inflamação; dano tecidual; flavonoides; quercetina; mieloperoxidase; elastase